Sounds like the Anthropocene: Alice Oswald's water-stressed, Homeric verse. Issue 1 (2nd January 2023) - Chisholm, Dianne
ABSTRACT: Alice Oswald's two books of Homeric verse, Memorial and Nobody, excavate the Iliad and the Odyssey, respectively, for sounds other than those man-glorifying songs of war and adventure made classical by literary tradition. They stress what Oswald calls the fluid, fleeting "livingness" of oral poetry that literary culture arguably deadens in its efforts to standardise and monumentalise Homer' s heroic narrative. To adjust the poetic balance between livingness and lastingness, Oswald distils Homer's narrative to its evanescent and/or atmospheric elements and she foregrounds those diluvial clamours which repeatedly drown out the hero's boasts and shouts, dampen his immortal aspirations and dissolve his bronze-clad psyche. This essay shows how Oswald's recovery of Homer's oral poetry in modern English verse concerns our approach to Anthropocene turbulence wherein we, her readers, might find ourselves adrift. It examines Oswald's strategy of stressing Homer's aquatic fluency at the expense of his heroic-anthropocentric-narrative and in view of Anthropocene philosophy that calls for a shift from imperial, instrumental thinking about water as an exploitable global resource to empathic thinking with water as a companion, supra-human, species.